2018
DOI: 10.1149/2.0611811jes
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Tortuosity of Porous Li-Ion Battery Electrodes: Comparing Polarization-Interrupt and Blocking-Electrolyte Methods

Abstract: Ionic mass transport including electrolyte diffusivity and conductivity depends on the geometric tortuosity of the electrode. This paper compares two experimental methods that determine tortuosity based on diffusivity or conductivity. The polarization-interrupt method previously developed by our group determines tortuosity in terms of effective diffusivity. The blocking-electrolyte method proposed by Gasteiger and coworkers determines tortuosity in terms of effective ionic conductivity and is analyzed using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(87 citation statements)
references
References 31 publications
2
84
1
Order By: Relevance
“…5, R ion can also be determined approximately since the length of the 45°sloped region spans across approximately R ion /3 along the real axis. 19 Likewise, Pouraghajan et al 20 showed different methods to quickly estimate R ion that all provide a reasonable estimate with minor discrepancy as compared to using the fit of Eq. 4.…”
Section: Symmetric Cell Methods For Porous Electrodes (Escm)mentioning
confidence: 99%
See 4 more Smart Citations
“…5, R ion can also be determined approximately since the length of the 45°sloped region spans across approximately R ion /3 along the real axis. 19 Likewise, Pouraghajan et al 20 showed different methods to quickly estimate R ion that all provide a reasonable estimate with minor discrepancy as compared to using the fit of Eq. 4.…”
Section: Symmetric Cell Methods For Porous Electrodes (Escm)mentioning
confidence: 99%
“…Malifarge et al 18 developed a more general analytical expression of the symmetric cell impedance that takes into account an arbitrary electronic resistance of the conductive matrix. More recently, Pouraghajan et al 20 developed a generalized TLM that takes into account additional possible sources of impedance, such as a contact resistance with the current collector, the charge-transfer resistance, and the electronic resistance of the electrode solid phase.…”
Section: Symmetric Cell Methods For Porous Electrodes (Escm)mentioning
confidence: 99%
See 3 more Smart Citations